Corporate social responsibility of multinational corporations in developing countries : perspectives on anti-corruption / Adefolake Adeyeye. - Adeyeye, Adefolake, 1972- (Cambridge University Press, 2012)
The increasing importance of CSR means that companies must consider multi-stakeholder interests as well as the social, political, economic, environmental and developmental impact of their actions. However, the pursuit of profits by multinational corporations has led to a series of questionable corporate actions and the consequences of such practices are particularly evident in developing countries. Adefolake Adeyeye explores how CSR has evolved to aid the anti-corruption campaign. By examining voluntary rules applicable for curbing corruption, particularly bribery and analysing the domestic and extra-territorial laws of Nigeria, United Kingdom and the United States for holding corporations liable for bribery, she assesses the adequacy of international law's approach towards corporate liability for bribery and explores direct corporate responsibility for international corruption. The roles of corporate governance, global governance and civil liability in curbing corporate corrupt practices are given special focus.